Recent clinical trials with stem cells to slow or reverse normal aging processes - Garay, Ricardo P. (Frontiers in Aging, 2023)
Aging is associated with a decline in the regenerative potential of stem cells. In recent years, several clinical trials have been launched in order to evaluate the efficacy of mesenchymal stem cell interventions to slow or reverse normal aging processes (aging conditions). Information concerning those clinical trials was extracted from national and international databases (US, EU, China, Japan, and World Health Organization). Mesenchymal stem cell preparations were in development for two main aging conditions: physical frailty and facial skin aging. With regard to physical frailty, positive results have been obtained in phase II studies with intravenous Lomecel-B (an allogeneic bone marrow stem cell preparation), and a phase I/II study with an allogeneic preparation of umbilical cord-derived stem cells was recently completed. With regard to facial skin aging, positive results have been obtained with an autologous preparation of adipose-derived stem cells. A further sixteen clinical trials for physical frailty and facial skin aging are currently underway. Reducing physical frailty with intravenous mesenchymal stem cell administration can increase healthy life expectancy and decrease costs to the public health system. However, intravenous administration runs the risk of entrapment of the stem cells in the lungs (and could raise safety concerns). In addition to aesthetic purposes, clinical research on facial skin aging allows direct evaluation of tissue regeneration using sophisticated and precise methods. Therefore, research on both conditions is complementary, which facilitates a global vision.